Les intellectuels et le Parti Ouvrier Belge - Vandervelde, Emile; Spaak, Paul-Henri; Van Roosbroeck, Joseph Louis (Bruxelles: POB, 1926)
"Emile Vandervelde, P.-H. Spaak ; Avant-propos Jos. Van Roosbroeck Collectie Vrijzinnige Werkmansbibliotheek"